Post-fire behaviour and resistances of square recycled aggregate concrete-filled stainless steel tube stub columns - Wang, Ziyi (2024)
Experimental and numerical studies on the cross-section compressive behaviour and residual resistances of square recycled aggregate concrete-filled stainless steel tube (RACFSST) stub columns after exposure to fire are reported in this paper. An experimental programme was firstly carried out on twelve stub column specimens with three recycled coarse aggregate replacement ratios (0%, 35% and 70%) after exposure to the ISO-834 standard fire for 0 min (i.e. at ambient temperature), 15 min, 30 min and 45 min. The test results, including load–end shortening curves, failure loads and failure modes, were presented, with the initial compressive stiffness and confinement effect analysed. The experimental programme was followed by a numerical modelling programme, where thermal and mechanical finite element models were developed and validated against the test results and afterwards used to conduct parametric studies to generate additional numerical data over a wide range of cross-section dimensions. Based on the test and numerical data, the relevant design rules for square natural aggregate concrete-filled carbon steel tube stub columns at ambient temperature, as specified in the European code, Australia/New Zealand standard and American specification, were evaluated, using post-fire material properties, for their applicability to square RACFSST stub columns after exposure to fire. The evaluation results generally revealed that the European code and Australian/New Zealand standard led to a good level of design accuracy, while the American specification resulted in slightly conservative post-fire cross-section compression resistance predictions.